Pengaruh Model Pembelajaran Kooperatif Tipe Think Pair Share Berbantuan LKPD Terhadap Pemahaman Operasi Bentuk Aljabar Pada Siswa Kelas VII SMPN 13 Mataram Tahun 2021/2022 - Bayu Saputra; Baidowi Baidowi; Muhammad Turmuzi; Syahrul Azmi (Griya Journal of Mathematics Education and Application, 2022)
Success in learning mathematics can be seen from understanding students' initial mathematical concepts, but a low average score is an indication of difficulties in understanding mathematical concepts related to algebraic operations. This study aims to determine the effect of cooperative learning models Think Pair Share (TPS) type assisted by student worksheets (LKPD) on students' understanding of algebraic operations. The research design used was Pre-Experimental Design (Non Design) in the form of One-Group Pretest-Posttest Design. The population in this study was all class VII, while the selected sample was class VIIA as the control class and class VIIB as the experimental class. Data on the ability to understand different concepts were taken using a pretest-posttest instrument in the form of essay questions. Before further analyzing the results of the pretest-posttest, the two classes were first tested for normality and homogeneity. The results of the hypothesis test show that = 0.441 < = 1.96 which means Ho is accepted, so that there is a difference between understanding the operation of algebraic forms in the experimental and control classes or in other words there is no effect of the TPS type cooperative learning model assisted by LKPD on understanding the operation of the form. algebra to students. This indicates that learning with the TPS type cooperative learning model assisted by LKPD allows students to achieve conceptual understanding where indicators are to restate concepts, classify objects according to certain properties, state concepts in various forms of mathematical representation, use, utilize and choose procedures. or certain operations and apply concepts